(untitled) (CIPEEX, 2025)
The present study aims to analyze the principle of insignificance in Brazilian Criminal Law, with a particular focus on its applicability in cases of recidivism. To this end, both objective and subjective criteria that support the application of this principle were examined, as well as the jurisprudential divergences between the Federal Supreme Court (STF) and the Superior Court of Justice (STJ) regarding its admissibility in the context of repeated offenses. Methodologically, the research was carried out through bibliographic review and case law analysis, adopting a qualitative approach with descriptive and explanatory character. It was found that, although the principle of insignificance operates as an exclusion of typicity, promoting a minimal and proportional Criminal Law, its application in situations involving recidivism faces resistance in part of the jurisprudence especially from the STJ, which tends to prohibit its use when criminal habituality is present. Conversely, the STF, in exceptional cases, has admitted the application of the principle even to repeat offenders, provided that minimal offensiveness of the conduct, absence of social dangerousness, and the insignificance of the harm to the legally protected interest are demonstrated. It is concluded that the careful application of the principle of insignificance is essential to avoid disproportionate punishments, reduce unnecessary imprisonment, and ensure the protection of fundamental rights, in line with the principles of proportionality, human dignity, and minimal intervention.